PEDAGOGIA DIALÓGICA DE AFETO E LIBERTAÇÃO: UMA REFLEXÃO A PARTIR DA PRÁTICA DA PROFESSORA LUANA TOLENTINO - Isabelle Rocha Nobre (TRF2, 2019)
Freire perceives reality as a process, an eternal becoming, in which solidarity between individuals and the world is an indispensable factor for true thinking and, consequently, for true dialogue. However, in order for this dialogue to succeed, it warns us that one can not do without everyone having a voice, that is, if an individual, or group of individuals, is in the condition of being oppressed in his limited freedom of speech, while the other denies this the right to say the word, there is no possibility of dialogue between them. Therefore, it is necessary that everyone first conquer the right to the necessary spaces of speech so that among all there may be an act of solidarity and plural creation. However, although the damage caused by the production of exclusive knowledge is easily observable, the mechanisms to change such a framework are little applied. The present work seeks to demonstrate an alternative of dialogic education based on the affection implemented by a Minas Gerais teacher in Fundamental Education through feminist, antiracist and inclusive pedagogical practices.